PERAN DINAS PARIWISATA DIY DALAM MENGEMBANGKAN KAWASAN PANTAI SELATAN YOGYAKARTA MELALUI EVENT OLAHRAGA KEDIRGANTARAAN JOGJA AIR SHOW - , FIQIH AGNES PUTRI; , Ghifari Yuristiadhi, SS. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final project examines the role of Dinas Pariwisata DIY to develope Regions Southern Beach of Yogyakarta by Sports Event Jogja Air Show. This research aims to analyze the role of Dinas Pariwisata DIY to develope Regions Southern Beach of Yogyakarta by Sports Event Jogja Air Show. To find out what the role of Dinas Pariwisata DIY to Develope Regions Southern Beach of Yogyakarta, to know how to work in implementing the Tourism Office of Jogja Air Show Event and what the problems that they face it, To determine the impact on communities around South Beach with the implementation of the Event Jogja Yogyakarta Air Show . The method used is descriptive research method, is to find, collect data, analyzes, and conclusions. The method of data collection in the form of direct observation at the time of the Event Jogja Air Show take place, interview with informants who can provide accurate information, and become participants in Jogja Air Show event. The results shows that the role of Dinas Pariwisata DIY to Develope Regions Southern Beach of Yogyakarta by Sports Event Jogja Air Show has an important role in the implementation of Air Show Event Jogja. The conclusion is the convening of Jogja Air Show Event with Location Parangtritis beach, Parangkusumo beach, and location adjacent to the Depok Beach has culinary seafood, it will automatically have a positive impact the local economic.